Solve for F: C=5/9(F-32)

multiply by 9
9C = 5(F-32)
9C = 5F - 160
9C + 160 = 5F
5F = 9C + 160
F + (9/5)C + 32

## Just a small typo in the last post. Instead of

F + (9/5)C + 32

Change F + (9/5)C + 32 to
F = (9/5)C + 32.

## Of course, I'm here to help you with that! The equation you provided is used to convert temperature from Fahrenheit (F) to Celsius (C). To solve for F, we'll follow a few steps.

Step 1: Distribute 5/9 to the expression inside the parentheses:

C = 5/9 * F - 5/9 * 32

Simplifying:

C = 5/9 * F - 160/9

Step 2: Move the constant term (-160/9) to the other side of the equation to isolate the F term:

C + 160/9 = 5/9 * F

Step 3: To get F by itself, we need to get rid of the fraction. Multiply both sides of the equation by 9/5:

(9/5)(C + 160/9) = F

Expanding and simplifying:

(9/5)C + (9/5)(160/9) = F

(9/5)C + 32 = F

This gives us the solution for F in terms of C. Therefore, to convert temperatures from Celsius to Fahrenheit, you can use the equation F = (9/5)C + 32.